Studi Eksperimen Pengaruh Kecepatan Aliran dengan Penambahan Insert Twisted Tape terhadap Performa Double Pipe Heat Exchanger - Aji, Pandu Gautama; Amalia, Rif?ah; Safitra, Arrad Ghani (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The double pipe heat exchanger (DPHE) is one type of heat exchanger (HE) that is commonly used in industrial applications such as electricity generation, petrochemical industry, process industry, and other industries. The double pipe heat exchangers are commonly used because of low design costs and maintenance costs. The need to achieve optimal double pipe heat exchanger performance, this research will examine the optimization of double pipe heat exchanger performance by varying fluid flow velocity and adding twisted tape insert with a twist ratio (H/D) = 6 in terms of Nusselt number (Nu), friction factor (f), and effectiveness (?). The test is carried out with fluid in the form of water and fluid flow velocity variations are 2.5, 3.5, 4.5, 5.5, and 6.5 LPM. The experimental results show that the Nusselt number value and effectiveness have increased with increasing fluid flow velocity. While the friction factor value decreases with increasing fluid flow velocity. The increase in Nusselt numbers was 2.14 times and the effectiveness value was 8.69%. While the value of the friction factor decreased by 55%. The optimum fluid flow velocity obtained from the results of the study is 6.5 LPM with Nusselt number, friction factor, and effectiveness reaching 48.43; 0.27; and 0.259.